Uncoupling Protein 2 in Cardiovascular Health and Disease - Tian, Xiao Yu; Ma, Shuangtao; Tse, Gary; Wong, Wing Tak; Huang, Yu (Frontiers in Physiology, 2018)
Uncoupling protein 2 (UCP2) belongs to the family of mitochondrial anion carrier proteins. It uncouples oxygen consumption from ATP synthesis. UCP2 is ubiquitously expressed in most cell types to reduce oxidative stress. It is tightly regulated at the transcriptional, translational and post-translational levels. UCP2 in the cardiovascular system is being increasingly recognized as an important molecule to defend against various stress signals such as oxidative stress in the pathology of vascular dysfunction, atherosclerosis, hypertension and cardiac injuries. UCP2 protects against cellular dysfunction through reducing mitochondrial oxidative stress and modulation of mitochondrial function. In view of the different functions of UCP2 in various cell types that contribute to whole body homeostasis, cell type-specific modification of UCP2 expression may offer a better approach to help understanding how UCP2 governs mitochondrial function, reactive oxygen species production and transmembrane proton leak and how dysfunction of UCP2 participates in the development of cardiovascular diseases. This review article provided an update on the physiological regulation of UCP2 in the cardiovascular system, and also discussed the involvement of UCP2 deficiency and associated oxidative stress in the pathogenesis of several common cardiovascular diseases. Drugs targeting UCP2 expression and activity might serve another effective strategy to ameliorate cardiovascular dysfunction. However, more detailed mechanistic study will be needed to dissect the role of UCP2, the regulation of UCP2 expression, and the cellular responses to the changes of UCP2 expression in normal and stressed situations at different stages of cardiovascular diseases.